KONSELING SEBAGAI ALTERNATIF PENANGGULANGAN PERILAKU MALADAPTIF REMAJA DEPRIVASI PARENTAL - Zaenal Abidin (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2010)
Teenager’s deprivational maladaptif is caused by broken home or death parenting among others, or the worstcondition’s in some families. Most of the teenagers have very hard psychological burdened after they parent was sparated each other.They were lost of full affection, guidance and counseling, taken care, sense of safety, and the bright future. By these families conditionsmost of the teenagers are disturbed their psychological development in all their life. By this case made some teenagers lost of emotionalcontroll, event their attitudes and behaviors unfamiliar and maladaptives as balancing compensation by unfavourable condition in theirfamilies. So, to save the maladaptives teenagers, counseling activities is very needed to assist them finding some accurate alternatives insolving their daily problems. By these ways at list their burdened will be more minimize and get them to study how tobe out of theirproblem, and study how to face the realities either those problem is very much unfavourable. And the end the teenagers have morecapable and potential to face their life rationally and able to see the brigt future